Review on the integration of high-temperature heat pumps in district heating and cooling networks. (15th January 2022) - Barco-Burgos, J.; Bruno, J.C.; Eicker, U.; Saldaña-Robles, A.L.; Alcántar-Camarena, V.
Abstract: The integration of heat pumps into DHC (District Heating and Cooling) networks provides significant environmental and performance improvements, an innovative and profitable solution for different decarbonizing sectors. This work reviews different district heating and cooling networks and the integration of high-temperature commercial heat pumps. Likewise, it describes placement options and connection modes of a heat pump unit in DHC networks, identifying twelve generic configurations of heat pumps and how they can be integrated into DHC systems, where four (4) of them have not been studied in the literature. The 3G, and 4G, are the most common district heating and cooling network generations for reference conditions reviewed. When considering a case where a central heat pump and CHP plant were located in the DHC network, the resulting coefficient of system performance (COSP) was in the range of 3–4 for commercial equipment with a range of coefficients of performance (COP) between 2 and 6. Using local HPs in the fourth and fifth-generation district heating networks, the resulting COSP was in the range of 0.95–1.5 for commercial equipment with a range of coefficients of performance (COP) between 2 and 6. Finally, for individual HPs in the district heating and cooling network, the resulting COSP was in the range 3–4 for commercial equipment with a range of coefficients of performance (COP) between 2 and 8. Highlights: Literature review of configurations to integrate HPs into district heating and cooling network. Classification and description of possible heat pump configuration in district heating networks. Placement and connection modes of heat pump units in a district heating and cooling network.